A Greener Approach to Oxazolidinone Synthesis Using a Ternary Deep Eutectic Solvent. Issue 17 (3rd May 2022) - Ahmadi, Faezeh; Nejad, Masoumeh Jadidi; Shariatipour, Monire; Heydari, Akbar
Abstract: By employing a ternary and environmentally benign deep eutectic solvent comprising choline chloride, glycerol, and aluminum chloride hexahydrate(ChCl/Glycerol/AlCl3 .6H2 O) as the catalyst and reaction media, three component reaction of epoxides, amines and dimethyl carbonate has been accomplished, which allows for the efficient construction of various 3, 5‐disubstituted oxazolidinones, important scaffolds in small molecule drug discovery. Simple reaction conditions and the use of green and sustainable materials and reagents make this a straightforward and practical methodology for obtaining various oxazolidinones. Abstract : A ternary deep eutectic solvent comprising choline chloride, glycerol, and aluminum chloride hexahydrate(ChCl/Glycerol/AlCl3 .6H2 O) as the catalyst and reaction media has been employed for the three component reaction of epoxides, amines and dimethyl carbonate to provide various 3, 5‐disubstituted oxazolidinones